2006
DOI: 10.1111/j.1551-2916.2005.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn, Sr, and Y Addition on Electrical Properties of PZT Thin Films

Abstract: We have investigated methods to increase the efficiency of piezoelectric micromachined ultrasonic transducers (pMUTs). pMUTs are driven by a thin piezoelectric layer on a Si membrane. The efficiency of pMUTs can be increased using a film with better ferroelectric properties. We have used Zn, Sr, and Y doping on PZT-based thin films along the morphotropic phase boundary (MPB) composition to increase their piezoelectric properties. The results obtained were then extended to compositions on both sides of the MPB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…0.5 M metallorganic precursor solution was prepared via sol-gel method using 2-methoxy ethanol as a solvent and lead acetate tri-hydrate, titanium isopropoxide (97%), zirconium n-propoxide (70%, w/w, in propanol) as the starting materials. Further details of the film preparation can be found in reference [11].…”
Section: Fabrication Of Pmutsmentioning
confidence: 99%
See 1 more Smart Citation
“…0.5 M metallorganic precursor solution was prepared via sol-gel method using 2-methoxy ethanol as a solvent and lead acetate tri-hydrate, titanium isopropoxide (97%), zirconium n-propoxide (70%, w/w, in propanol) as the starting materials. Further details of the film preparation can be found in reference [11].…”
Section: Fabrication Of Pmutsmentioning
confidence: 99%
“…Improvement in pMUTs performance can be achieved through optimization in material and design variables. Research work focusing on material optimization [11] and FEA analysis [12] reported previously by our group has helped us to narrow down different design parameters. The present work is focused on optimization of top electrode design.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various ferroelectric materials, PZT is one of the most attractive due to its large remnant polarization (Pr) and excellent reliability (imprint, retention, fatigue) (Seo et al [15]). Effects of various doping elements, such as La [16,17], Nb [18], Fe [19], Mn [20], Sb [21], Ca [22] and Sr [23], in PZT thin films have been extensively researched. One particular effect is that the aliovalent La 3+ ion alters the macroscopic properties of PZT thin films, from normal ferroelectric to relaxor ferroelectric type (Prabu et al [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Abhishek Palakoti et al [5] (100) substrates: (1) Each layer was spin-coated at 3000 rpm for 30 s and baked at 180 • C for 5 min in an oven to remove the residual solvents; (2) The heat treatment was performed with a rapid thermal process (RTP) at 350 • C for 5 min to pyrolyze the organic materials;…”
Section: Introductionmentioning
confidence: 99%